Outcome of the Pre-Kidney Transplantation Clinic at Phra Nakhon Si Ayutthaya from June 2012 - September 2015 - พัววิไล ธิติยา (Journal of Preventive Medicine Association of Thailand, 2019)
Descriptive research has been studied on rate of KT (Kidney Transplantation) in ESRD (End Stage Renal Disease) patients. Retrospective analysis from medical records of patients who received management from pre-kidney transplantation clinic in Phra Nakhon Si Ayutthaya hospital during June 2012 and September 2015. Patient characteristic, recipient characteristic, type of KT, waiting time for KT, living donor characteristic were collected. There were 87 attendances. The result showed that mean of age were 43.78 11.38 Year. Most expressed a desire to receive kidney transplant from cadaveric donor 79.3%. This study found KT rate was 10.3% (Female 5 cases, Male 4 cases). LRKT (Living related kidney transplantation) was 66.7% and DDKT (Deceased donor kidney transplantation) was 33.3%. The mean age of DDKT patients (44.72 8.11 years) was higher than LRKT patients (35.7 15.12 years). Waiting time for kidney transplant of patients who received kidneys from cadaveric donor since the start of dialysis (44.4 5.9 months) and from referral (18.7 4.8 months) longer than patients who received kidneys from living donors (38.9 22.9 months, 16.8 8.6 months). The recipient does not receive any dialysis. The number of living kidney donors were 6 cases (Female : Male = 1 : 1). Mean age of living kidney donor was 40.06 13.63 years. Majority is associated with the recipient’s blood relationship (66.7%). All living kidney donors can still work normally. Therefore, the knowledge of KT through and complete to patients and relatives, Selection of CKD patients who did not had contraindication for KT, patient care while awaiting a kidney transplant and increase the number of kidneys donated from living donors and cadaveric donor. It improves the chances that ESRD patients get kidney transplants increased.